Pengembangan Media Pembelajaran Matematika Berbantuan FlipBook Berbasis Problem Based Learning yang Memfasilitasi Kemampuan 4C Siswa - Khafidhoh, Masruroh; Mahmudah, Wilda (Universitas Dr. Soetomo, 2022)
From several studies, it was found that many students still had difficulties in three-dimensional geometry subject matter. In addition, students also have difficulty understanding abstract mathematical concepts, especially in three-dimensional materials. So the purpose of this study is to produce a flipbook-assisted learning media for mathematics based on problem-based learning that facilitates students 4C abilities in terms of validity and practicality. By this PBL learning approach students are expected to be able to think critically, have problem solving skills and getting knowledge about the essence of three-dimensional materials. This Flipbook-assisted media has an attractive design, equipped with learning videos and students can easily access the materials only through a link. This type of research is development research using the ADDIE’S model. The research instrument consisted of an observation sheet, a validation sheet and a student response questionnaire. The subjects of this study were 30 students of class XI MIPA-1 SMA Assa'adah Bungah Gresik. The validation results from media experts obtained an average value of 3.63 so that the media was said to be very valid and the validation results from material experts obtained an average value of 3.79 so that the media in the criteria were very valid. Then the result of the students respons questionnaire obtained an average of 81.33% with very practical criteria. So, based on the result of the study, it was found that the flipbook-assisted learning media based on problem-based learning that facilitates students 4C abilities is very valid, very practical and feasible to use. Keywords: Mathematics Learning Media, Flipbook, Problem Based Learning, 4C Ability.